Absorption Enhancement in Thin Organic Solar Cells With MoO3/Ag/MoO3 Transparent Anode Based on Short-Pitched Metallic Grating - Ye Zhang; Yanxia Cui; Ting Ji; Yuying Hao; Furong Zhu (IEEE Photonics Journal)
The multilayer film consisting of MoO3/Ag/MoO3 (shortened as MAM) is very promising as an alternative of indium-tin oxide (ITO) to work as the transparent anode in organic solar cells (OSCs). In MAM-based thin OSCs, the absorption of light is quite poor. Here, we propose to apply a short-pitched metallic grating into the MAM-based OSC for improving the absorption in its thin active layer. Numerical calculations reveal that the obtained enhancement of integrated absorption in the active layer is more than 500% with respect to the equivalent planar control. The field distributions at the two peaks of the normalized absorption spectrum indicate that propagating surface plasmon polaritons (SPPs), as well as the horizontal metal-insulator-metal (MIM) waveguide mode, play the main role of trapping light into the active material. It is expected that the proposal could contribute to the development of the efficient ITO free thin OSCs.